Online Education as a Learning Strategy in the COVID-19 Global Pandemic (Comparative & International Education Series, 2022)
This paper is a result of participation in the 2020 STAR Scholars Conference panel that covered the topic of Learning Strategies in the COVID-19 Global Pandemic; it focuses primarily on practices and strategies in higher education. The paper discusses the advantages, disadvantages, challenges, and opportunities of online learning and explores research on the efficacy of online learning as a tool and strategy in education. Institutional leadership qualities to bring about excellence in online learning are also included in the paper.